Pengaruh jamur tiram putih (pleurotus ostreatus) terhadap kadar glukosa darah, profil lipid dan kadar MDA pada tikus (rattus norvegicus) diabetes melitus - Purbowati, Purbowati; Johan, Andrew; RMD, RA Kisdjamiatun (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background : Diabetes mellitus is a chronic disease caused by acquired deficiency in insulin production by the pancreas, or by the ineffectiveness of using the produced insulin. Oyster mushroom (Pleurotus ostreatus) can help lower blood glucose levels, improve lipid profile and reduce levels of MDA.Objective : to analyze the effect of oyster mushroom on blood glucose levels, lipid profile and MDA levels in STZ induced rats as type 1 DM model. Methods : thirty Sprague Dawley rats were randomly divided into 3 groups: one positive group (1) and two treated group which received 100 mg/kgBB (2) and 200 mg/kgBB (3) oyster mushroom extract, respectively. The interventions were carried out for 30 days. The examination of blood glucose levels, lipid profile and MDA levels was before and after the intervention. The differences inthe datapre-post interventions were analyzed by paired t-test, whereas the differences between the groups were analyzed by one-way ANOVA and kruskal wallis followed by post hoc analysis. Results : the treatment group experienced a decrease in blood glucose levels, total cholesterol, LDL cholesterol, triglycerides, MDA and an increase in HDL cholesterol levels post-intervention (p < 0,001). Oyster mushroom extract with the dose of 200 mg/kg was more effective in lowering blood glucose levels, MDA levels and improving lipid profiles (p < 0,001).Conclusion : Oyster mushrooms administration lowers blood glucose levels, total cholesterol, LDL cholesterol, triglycerides, MDA and increases HDL cholesterol levels.Â